Cognitive psychology and its implications - Anderson John R (New York Worth, 2004)
the book emphasizes an information processing approach to the field, but offers thorough coverage of the cognitive neuroscience approach as well (extensively updated for this edition).This Sixth Edition features a new two-color design and an expanded art
Keywords: Cognition; Cognitive psychology